ANALISIS PENGARUH DAYA TARIK IKLAN, DESAIN PRODUK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE VIVO DI MILLENIUM ITC CENTRE MEDAN - Fadhilah Anisyah; Hernawaty Hernawaty; Miftah El-Fikti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The purpose of this study was to determine the analysis of the influence of the attractiveness of advertising, product design and lifestyle on the purchasing decision of Mobile Vivo at the Millennium Itc Center Medan. The high level of competition causes consumers to act selectively in making purchasing decisions. In making consumer purchasing decisions. Based on this matter, the problem in this study was the decrease in the number of Vivo handphone users in August amid an increase in the number of users in each month. The problem with the policy of attractiveness of advertising, is that there is still a lack of promotional media used by companies. While the problems in product design, the features of the vivo handphone marketed by the company are still not good compared to other products. So that with the existence of these problems, the decision to purchase the company's Vivo handphone also declined. The approach used in this study is to use a type of quantitative descriptive research. The total population in this study was 382 customers. The sample used in this study was 79 people. This research uses t test, F test, determination test and multiple linear regression analysis. The conclusion in this study is the attractiveness of advertising and product design affect the purchasing decision of the Vivo handphone at the Millennium Ict Center Medan. While lifestyle influences negatively on the purchase decision of the Vivo handphone at the Millennium Ict Center Medan.Keywords: Influence, Attractiveness, Advertising, Design, Product, Style.